Extra-gastrointestinal manifestations of inflammatory bowel disease may be less common than previously reported - Card, Timothy R.; Langan, Sinéad M.; Chu, Thomas P.C. (Springer Verlag, 2016)
Extra-intestinal manifestations are well recognized in inflammatory bowel disease (IBD). To what extent the commonly recognized extra-intestinal manifestations seen in IBD patients are attributable to IBD is, however, not clear due to the limited number of controlled studies published.